KAMPANYE GERAKAN MASYARAKAT HIDUP SEHAT (GERMAS) DI KABUPATEN JENEPONTO - Dahlan, Akbar Farid (Istiqra: jurnal hasil penelitian, 2022)
This research aims to find out and explain the healthy living community movement (GERMAS) campaign in Jeneponto Regency while the method used in this research is qualitative with a phenomenological approach. Meanwhile, the data in this research used data collection techniques of in-depth interviews and observations with informants. Based on the data that has been collected, the results of this research show that good community behavior for disease prevention in the GERMAS program in Jeneponto district starts from the intention as a form of early disease control. Suggestions for the community to actively participate in the GERMAS program by taking part in every activity held by the Community Health Center team